Evaluation of the flexural strength and serviceability of geopolymer concrete beams reinforced with glass-fibre-reinforced polymer (GFRP) bars. (15th October 2015) - Maranan, G.B.; Manalo, A.C.; Benmokrane, B.; Karunasena, W.; Mendis, P.
Highlights: The behaviour of geopolymer concrete beams with GFRP bars was evaluated. Bar diameter and anchorage type have insignificant effect on beam's behaviour. The serviceability performance is enhanced with higher reinforcement ratio. The sand-coated GFRP bars have adequate bond strength to geopolymer concrete. ACI-440.1R-06 and CSA S806-12 underestimated the flexural capacity of the beams. Abstract: Geopolymer concrete reinforced with glass-fibre-reinforced polymer (GFRP) bars can provide a construction system with high durability, high sustainability, and adequate strength. Few studies deal with the combined use of these materials, and this has been the key motivation of this undertaking. In this study, the flexural strength and serviceability performance of the geopolymer concrete beams reinforced with GFRP bars were evaluated under a four-point static bending test. The parameters investigated were nominal bar diameter, reinforcement ratio, and anchorage system. Based on the experimental results, the bar diameter had no significant effect on the flexural performance of the beams. Generally, the serviceability performance of a beam is enhanced when the reinforcement ratio increases. The mechanical interlock and friction forces provided by the sand coating was adequate to secure an effective bond between the GFRP bars and the geopolymer concrete. Generally, the ACI 4401.R-06 and CSA S806-12 prediction equations underestimate the beam strength. The bending-moment capacity of the tested beams was higher than that of FRP-reinforced concrete beams from the previous studies.